2021
DOI: 10.1103/physrevlett.126.103602
|View full text |Cite
|
Sign up to set email alerts
|

Remote Individual Addressing of Quantum Emitters with Chirped Pulses

Abstract: We propose to use chirped pulses propagating near a band gap to remotely address quantum emitters. We introduce a particular family of chirped pulses that dynamically self-compress to subwavelength spot sizes during their evolution in a medium with a quadratic dispersion relation. We analytically describe how the compression distance and width of the pulse can be tuned through its initial parameters. We show that the interaction of such pulses with a quantum emitter is highly sensitive to its position due to e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…In light of the reported results, we believe that quantum networks made of superconducting qubits and wavguides constitute a promising platform to implement quantum operations on both long-distant (inter-node) and short-distance (intranode) quantum processors. Furthermore, we expect further theoretical developments, such as chirping [52] and quantum control [35,36], to overcome the limitations induced by propagation and Stark shifts, and to further optimize the speed of state transfer. Now, for the case of propagation, we can expand the dispersion relation up to second order in the vicinity of the central frequency ω c ,…”
Section: Discussionmentioning
confidence: 99%
“…In light of the reported results, we believe that quantum networks made of superconducting qubits and wavguides constitute a promising platform to implement quantum operations on both long-distant (inter-node) and short-distance (intranode) quantum processors. Furthermore, we expect further theoretical developments, such as chirping [52] and quantum control [35,36], to overcome the limitations induced by propagation and Stark shifts, and to further optimize the speed of state transfer. Now, for the case of propagation, we can expand the dispersion relation up to second order in the vicinity of the central frequency ω c ,…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the first factor, Peñas et al [23] showed that the curvature of the dispersion relation in a quantum link sets stringent bounds on the ultimate state transfer fidelity. This affects potentially many experiments with microwave guides [17,18], photonic crystals [24,25] or spin waves [26,27]. As for the non-Markovian effects [28,29], these arise in the chirping of qubit-photon couplings, and manifest in distortions of the emitted wavepackets, which deviate from the predictions of the usual input-output theory.…”
Section: Introductionmentioning
confidence: 99%
“…[18,19] Specifically, a method was proposed and theoretically investigated for obtaining rectangular pulses. [20,21] This method relied on coherent control and free induction decay of low-frequency oscillations in nonlinear media. The quantum entanglement, maximum fidelity, quantum Fisher information, and the analytical spectrum formula of the rectangular pulses have been studied in detail.…”
Section: Introductionmentioning
confidence: 99%